KONSTRUKSI KECANTIKAN PEREMPUAN DALAM IKLAN DOVE VERSI BERAGAM KECANTIKAN SATU INDONESIA - Santika Dewi, Putu Ayu; Alit Suryawati, I Gusti Agung; Pascarani, Ni Nyoman Dewi (E-Jurnal Medium; Vol 1 No 1 (2019), 2019)
ABSTRACT Advertisement is a form of activity to promote an idea, product, or service that is conveyed by persuasion, one of them is by showing the aesthetic beauty of women. Beauty is pictured as a woman with slim waist, fair skin, and with long dark straight hair. However, the stereotype of beauty has been changing these days as shown in a Doveadvertisement Beragam Kecantikan Satu Indonesia version. By using qualitative research methods with the constructivist paradigm and Roland Barthes’ semiotics analysis, the researcher found a different construction of beauty in a Doveadvertisement Beragam Kecantikan Satu Indonesia version. The concept of beauty that is constructed in this advertisement refers to variety of women's beauty. It can be seen at the variety of sizes, hair styles, skin color, and age that is portrayed in this advertisement. This shows that the post-modern concept of beauty is referring to plurality, heterogeneity, and very subjective. Key Words           : Advertisement, Beauty, Construction, Women, Semiotics